RETRACTED: “Crisis Within the Walls”: Rise of Intimate Partner Violence During the Pandemic, Indian Perspectives - Nair, Vasundharaa S.; Banerjee, Debanjan (Frontiers in Global Women's Health, 2021)
The ongoing COVID-19 pandemic has been a social ‘un-equalizer’, besides being a global health threat. Gender inequality has been globally prominent during the outbreak and the consequent lockdown. While domestic abuse and intimate partner violence have increased due to chronic entrapment, overcrowding in families, enhanced substance use, distorted relationship dynamics, travel restrictions and reduced healthcare access, coercive sexual practices have also been on the rise. In low and middle-income countries, the lack of awareness, societal pressure, administrative apathy, fear of legal hassles and inadequate knowledge-attitude-practice related to help-seeking lead to under-reporting and mismanagement of domestic abuse, which can perpetuate its vicious cycle during the ongoing crisis. India, with its socio-culturally diverse population, has been one of the nations worst hit by the pandemic. With the rise in reports of gender-based violence on the premise of pre-existing gender inequality and minority stress, concerns behind “closed doors” are as threatening as the infection itself. With this background, the authors highlight the backdrop of domestic violence as a “hidden pandemic” during the COVID-19 crisis, drawing on perspectives from India and briefly reviewing the data from other nations. The role of mental health education and digital literacy as mitigating strategies is subsequently discussed.